Applying Bioporic Liquid Palm Industry Waste and Effect on Palm Oil Plant Growth and Dystrudepts Soil Physical Properties - Joehandra Joehandra; Nelvia Nelvia; Anthony Hamzah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
This study seeks to determine the impact of palm oil wastewater, the number of biopore holes, and their interaction on oil palm plant growth and Dystrudepts soil physical properties. This study was carried out between December 2019 and April 2019. This research was conducted using a 3x3 factorial experiment with a Randomized Block Design; each treatment was replicated three times, and each experimental unit contained three plants for 81 experimental plants. The first variable was the dosage of palm oil effluent, which consisted of 7.5 liter/plant/2 weeks, 10 liters/plant/2 weeks, and 12.5 liters/plant/2 weeks. The second factor had three levels: two biopore holes/plants, four biopore holes/plants, and six biopore holes/plants. Analysis of variance (ANOVA) was applied to the data. If the treatment is markedly different, a second test is conducted using the 5% level of the Honest Significant Difference (BNJ) test. (1) Palm oil mill effluent at a concentration of 7.5 liters/plant increased the total pore space. The effluent from a palm oil mill at a rate of 12.5 liters per plant decreases BD and PD while increasing final plant height, midrib length, leaf length, and chlorophyll content. (2) Adding two biopores per plant increased plant height, midrib length, and leaf width. The presence of four biopores per plant decreased BD and PD and increased leaf length and chlorophyll content. Six openings per plant biopores have an effect on increasing the total pore space, and (3) The interaction between LCPKS doses of 12.5 liters/plant and the number of biopores of 6 holes/plant decreases BD and increases total pore space, plant height, frond length, leaf length, and leaf breadth.